Optimizing the scavenging system for high efficiency and low emissions: a computational approach - Goldsborough, S. Scott, author; Mitchell, Charles S., advisor (Colorado State University. Libraries, 2002)
A free piston internal combustion engine operating on high compression ratio, HCCI combustion is being developed to significantly improve the thermal efficiency and exhaust emissions relative to conventional crankshaft-driven SI and Diesel engines. A two-stroke scavenging process recharges the engine and is key to realizing the efficiency and emissions potential of the device. To ensure that the engine's performance goals can be achieved the scavenging system was configured using Computational Fluid Dynamics, zero-dimensional and one-dimensional modeling, along with single step parametric variations. Visualization of the in-cylinder and port dynamics allowed the flow through the engine to be more completely understood and better controlled. Through a comprehensive study a wide range of design options were investigated including the use of loop, hybrid-loop and uniflow scavenging methods, different charge delivery options, and various operating schemes. Parameters such as the intake/exhaust port arrangement, valve lift/timing, charging pressure and piston frequency were varied. Operating schemes including a standard uniflow configuration, a low charging pressure option, a stratified scavenging geometry, and an over-expansion (Atkinson) cycle were studied. High scavenging and trapping efficiencies (-0.85, >0.99, respectively), as well as overall thermal efficiency and exhaust emissions were metrics by which the designs were evaluated. The computational results indicated that the loop and hybrid-loop arrangements are inadequate, however, the uniflow geometry can produce both high scavenging and high trapping efficiencies. The delivery tank pressure and temperature histories are important to enabling steady charging, high operating compression ratio and low pumping power consumption. Stratified scavenging and over-expansion operating schemes can significantly improve the efficiency of the engine cycle, through increased compression ratio (-24:1) (by more complete flushing) and additional blowdown recovery, respectively. However, the over-expansion arrangement was calculated to result in large cycle-to-cycle variability for slightly altered operating conditions. It was found that the in-cylinder flows are important to both NOx and short-circuiting emissions with inadequate mixing (and resulting temperature stratification) the predominant driver of NO production, and fuel penetration to the valve region the main cause of short-circuiting emissions. In addition, early auto-ignition of the charge by the hot residual gases can lead to reduced efficiency potential.
Keywords: mechanical engineering